Initial orienting to emotional faces in female adolescents with borderline personality disorder - Ceumern-Lindenstjerna, Ina-Alexandra von; Brunner, Romuald; Parzer, Peter; Mundt, Christoph; Fiedler, Peter; Resch, Franz (Psychopathology, 2010)
Background: Previous research has implicated a general hypervigilance for negative emotional words in adults with borderline personality disorder (BPD) as compared to healthy controls. The purpose of this study was to assess initial orienting to negative and positive emotional faces in female adolescents with BPD. Method: Adolescent patients with BPD (n = 30), adolescent patients with other psychiatric diagnoses (n = 29) and adolescent healthy comparison subjects (n = 29) were tested with the visual dot probe task to examine attentional orienting to emotional and neutral faces. Results: In contrast to the adolescent healthy comparison subjects, both the adolescent patients with BPD and the adolescent patients with other psychiatric diagnoses showed a stronger orienting to negative emotional stimuli. However, no differences were found between the clinical groups. Data regarding positive stimuli showed that BPD is not associated with a specific orienting to positive faces. Conclusions: These findings suggest that attentional orienting to negative faces is not specific to adolescent patients with BPD but also affects adolescent patients with other psychiatric diagnoses. Furthermore, no distortion in information processing concerning positive cues was observed in adolescent patients with BPD. If these findings were confirmed, further BPD research could no longer assume that BPD is specifically associated with distortions in initial orienting processes.
Gesehen am 28.06.2021